Oral propranolol in the treatment of infantile hemangioma: a case series of 50 infants. - Martínez Roca, C.; Rodríguez Ruíz, M.; Vilaboa Pedrosa, C.; Gómez Tellado, M.; Del Pozo Losada, J.; Martín Herranz, M.I. (European Journal of Pediatric Dermatology, 2014)
The aim of this study was to analyse the effectiveness and safety of oral propranolol in the off-label treatment of infantile hemangioma. A retrospective observational study carried out between August 2008 and June 2013 included all the patients diagnosed with infantile hemangioma who were prescribed propranolol. The data obtained were as follows: age, sex, diagnosis, risk factors, dose regimen, duration of treatment, effectiveness, side effects and clinical course in the six months after the end of treatment. Propranolol was prescribed to 50 children without cardiopulmonary risk factors and with suitable blood sugar levels. The initial dose of 0.5 mg/kg per day was gradually increased every 3 days to a maximum of 2 mg/kg/day. In all of the cases, the total daily dose was administered twice, every 12 hours. 94% of the patients responded to treatment. The remaining 6% did not respond to propranolol, even when the dose was increased. In the patients who responded to treatment, shrinkage of the tumor was observed in the first 3-7 days. The mean duration of treatment was 9.2 months. In two cases, tumor re-growth was observed after treatment was stopped. During the study period, 4 slight side effects were observed: 3 altered sleep patterns and 1 bronchospasm associated with a viral process.